The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2353/ajpath.2009.081037
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Expression of Colony-Stimulating Factor-1 and Colony-Stimulating Factor-1-Related Proteins Is Associated with Poor Prognosis in Gynecological and Nongynecological Leiomyosarcoma

Abstract: Previously, we showed that the presence of high numbers of macrophages correlates with poor prognosis in nongynecological leiomyosarcoma (LMS). In gynecological LMS, a similar trend was noted but did not reach statistical significance. Colony-stimulating factor-1 (CSF1) is a major chemoattractant for macrophages. Here we show that in a subset of LMS cases, CSF1 is expressed by the malignant cells. Previously, we found that CSF1 is translocated and highly expressed in tenosynovial giant cell tumors (TGCTs), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 38 publications
8
77
0
Order By: Relevance
“…The TME's role as a nonneoplastic component of tumors has been studied extensively in carcinomas but remains less well characterized in sarcomas. Consistent with the findings in carcinomas, we have previously shown that in LMS, a high density of TAMs predicts poor patient outcome, and that these TAMs are likely attracted to the primary tumor site by secretion of the macrophage chemoattractant colony-stimulating factor-1 (CSF1) by tumor cells (7,8). Moreover, in extrauterine LMS, we showed a correlation between CSF1 expression and a highly vascularized TME, consistent with the protumorigenic effects of TAMs (9).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The TME's role as a nonneoplastic component of tumors has been studied extensively in carcinomas but remains less well characterized in sarcomas. Consistent with the findings in carcinomas, we have previously shown that in LMS, a high density of TAMs predicts poor patient outcome, and that these TAMs are likely attracted to the primary tumor site by secretion of the macrophage chemoattractant colony-stimulating factor-1 (CSF1) by tumor cells (7,8). Moreover, in extrauterine LMS, we showed a correlation between CSF1 expression and a highly vascularized TME, consistent with the protumorigenic effects of TAMs (9).…”
supporting
confidence: 72%
“…TAM infiltration was likely mediated by expression of CSF1 by the tumor cells. In nongynecological LMS, the presence of TAMs was associated with increased vessel density, suggesting that the poor clinical outcome seen in these tumors could in part be because of increased vascularity mediated by TAMs (7)(8)(9). Hence, the M2 phenotype likely predominates in TAMs present in LMS tumors as it does in most, but not all, epithelial tumors.…”
Section: Discussionmentioning
confidence: 98%
“…We previously demonstrated that CD163 is a useful marker for detecting M2 cells on paraffinembedded surgical specimens (6), and high infiltration of M2 TAMs are associated with a poor clinical prognosis in patients with high grade glioma, cholangiocarcinoma, angioimmunoblastic T cell lymphoma, and renal cell carcinoma (7)(8)(9). Similar results have been reported in melanoma, follicular lymphoma, leiomyosarcoma, and pancreatic cancer (10)(11)(12). Therefore, it is speculated that the inhibition of macrophage polarization toward the M2 phenotype could represent a new strategy for anticancer therapy.…”
Section: Introductionsupporting
confidence: 67%
“…Conversely, the findings of the current study suggest that LMS is an inflammatory tumor type with high levels of T‐cell‐related gene expression, with several tumors demonstrating very strong expression of PD‐L1 and containing PD‐1‐expressing cells. Nevertheless, we suspect that combination therapy may be necessary to treat these tumors because other investigators have suggested that immunosuppressive tumor‐associated macrophages may be critical to immune evasion in these tumors 29, 41, 42. Combinations of checkpoint inhibitors with drugs aimed at depleting or modulating these cells may prove successful in providing durable responses for these patients.…”
Section: Discussionmentioning
confidence: 99%